Elektroda Graphite Pensil - Bismut untuk Menganalisa Timbal Secara Cyclic Voltammetry Menggunakan Potensiostat Berbasis Modul Psoc 5 Lp - Revalina Yulianti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Lead (Pb²⁺) heavy metal contamination in the environment requires a sensitive, rapid, and economical analytical method. This study aimed to determine the effect of electrolyte type, scan rate, and bismuth-modified pencil graphite type on the Pb²⁺ response using the cyclic voltammetry method and to evaluate electrode performance in water samples. The study was conducted using a PSoC 5 LP module-based potentiostat with bismuth-modified HB, 2B, and 4B pencil graphite working electrodes. The electrolyte solutions used were NaCl and acetate buffer at pH 7 with concentration variations of 0.1, 0.05, 0.01, 0.001, 0.0001, and 0.00001 M, while scan rates were varied at 50, 100, 150, and 200 mV/s within a potential range of +300 mV to -900 mV. Standard Pb(NO₃)₂ solutions with concentrations of 150-500 ppm were used for calibration curve preparation and electrode performance evaluation. The results showed that 0.1 M acetate buffer produced higher and more stable oxidation current responses than NaCl. The optimum scan rate was obtained at 200 mV/s with an oxidation current of 22 µA and %RSD of 3.69%, while 2B pencil graphite produced the optimum response with an oxidation current of 24 µA and %RSD of 5.27%. The oxidation calibration curve produced the regression equation y = 0.116x - 13.383 with an R² value of 0.9927, while the reduction curve produced the regression equation y = -0.0251x - 9.4619 with an R² value of 0.9839. The electrode exhibited a sensitivity of 3.69 µA ppm⁻¹ cm⁻², and a limit of detection (LOD) of 146.64 ppm, indicating good capability for detecting low concentrations of Pb²⁺. The %recovery value of 96.71% indicated good accuracy in water sample analysis. This study demonstrates that the bismuth modified pencil graphite electrode based on cyclic voltammetry is capable of detecting Pb²⁺ with good, stable, and sensitive responses.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Cyclic Voltammetry; bismuth-modified pencil graphite electrode; PSoC 5 LP potentiostat